Intercolony Avoidance Optimizes Foraging in Eciton burchellii Army Ants - Kunhart, Tom W.; Willson, Susan K. (Sociobiology, 2024)
Foraging individuals optimize spatial movement to maximize resource use in heterogeneous environments. Colonies of Eciton burchellii, a neotropical species of army ant, forage as an army, consuming broad arrays of arthropod and social insect prey. Prey depletion in foraging paths exacerbates resource heterogeneity for E. burchellii and may encourage colonies to avoid contact with recently raided areas. Colonies are known to turn in opposite directions more often than random from previous days’ foraging paths, which increases distances between recently raided areas. However, no evidence of colony avoidance of areas recently foraged by a conspecific colony has been presented. In this study, we analyze data collected in the Peruvian Amazon between 1998 and 2008 to examine colony spatial distribution using nearest-neighbor distance data. We found that colonies optimize movement by choosing foraging angles that deflect away from areas recently raided by conspecific colonies. In addition, we found that the observed nearest neighbor distance between E. burchellii colonies was more significant than expected if colonies were dispersed randomly. This dispersion pattern increases the distance between colonies and contributes to a spatial movement that optimizes foraging and decreases colony interactions at recently raided areas.